TA’LIM JARAYONIDA MOTIVATSIYANING O‘RNI VA UNI OSHIRISH YO‘LLARI (Ustozlar uchun, 2026)
This article examines the role of motivation in the educational process and explores effective ways to enhance it. It analyzes different types of motivation and their influence on students’ academic performance and engagement in learning activities. Particular attention is given to strategies for increasing students’ interest in learning, including the development of both intrinsic and extrinsic motivation. The study also highlights the importance of the teacher’s role, the use of interactive teaching methods, and the implementation of goal-oriented encouragement techniques to improve the overall quality of education.